ROSETTA STONE FOR DECIPHERING DEAZAPURINE BIOSYNTHESIS: PATHWAY FOR PYRROLOPYRIMIDINE NUCLEOSIDES TOYOCAMYCIN AND SANGIVAMYCIN - McCarty, Reid (2008)
Pyrrolopyrimidine nucleosides analogs, collectively referred to as deazapurines, are an important class of structurally diverse compounds found in a wide variety of biological niches. In this report, a cluster of genes from Streptomyces rimosus involved in production of the deazapurine antibiotics sangivamycin and toyocamycin was identified using forward genetics methods. The cluster includes toyocamycin nitrile hydratase, an enzyme that catalyzes the conversion of toyocamycin to sangivamycin. In addition to this rare nitrile hydratase, the cluster encodes a GTP cyclohydrolase I, linking the biosynthesis of deazapurines to folate biosynthesis, and a set of purine salvage genes, which presumably convert the guanine moiety from GTP to the adenine-like deazapurine base found in toyocamycin and sangivamycin. The gene cluster presented here could potentially serve as a “Rosetta stone” to inform on deazapurine biosynthesis in other bacterial species.